A CONCEPTUAL PAPER ON THE EFFECTS OF TECHNOSTRESS ON JOB PERFORMANCE AMONG TEACHERS WITH MODERATING ROLE OF TOXIC LEADERSHIP - Mohamad Haniff Bin Mohd Yasin; Ahmad Syahmi Ahmad Fadzil; Muhammad Bin Majid (Journal of Islamic, Social, Economics and Development, 2022)
Almost every job sector in this world is depending on Information, Communicationand Technology (ICT) including the academic sector. Similarly, the process of teaching,learning, research and administration using ICT are heavily utilized in the academicinstitution. Technology nowadays is continuously augmented in teaching and learning to enrichthe learners. Despite of ICT having many advantages, it can also create Technostress amongteachers when overused, lack of competency or fast-changing of ICT. Hence, technostress cansignificantly affect their job performance if not properly regulated. This study intends tohighlight the gap or the grey area of Technostress on job performance with the moderating roleof toxic leadership and boss phubbing among school teachers. The findings of this study showthe proposed framework derived from past studies and anchored the framework throughTransactional Theory of Stress. Additionally, the findings also highlighted the gap left by therecent research and presented relationships among the constructs. This research is hopeful tocontribute to the body of knowledge in exploring more on the effects of technostress on the jobperformance among the school teachers. Moreover, this research can give more insight torelevant ministry in regulating and mitigating the potential effect of technostress.